The Roles of Civil Society to Changing of Women Driving Policy In Saudi Arabia: Case Women2Drive Campaign - Rijal, Najamuddin Khairur; Khoirina, Rizka Zahrotun (Universitas Muhammadiyah Yogyakarta, 2019)
This paper examines the role of civil society, women activists, in an attempt to protest the prohibition of women driving policy by the government of Saudi Arabia. Using the concept of civil society, this paper shows that the efforts of women activists are conducted through Women2Drive campaigns by utilizing social media instruments. The results found that through a campaign in social media, Saudi women activists managed to push for a policy change of Saudi Arabian government to allow women driving.